2018
DOI: 10.1186/s13012-018-0786-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and use of computerised clinical decision support (CCDS) in emergency pre-hospital care: a qualitative study of paramedic views and experience using Strong Structuration Theory

Abstract: BackgroundComputerised clinical decision support (CCDS) has been shown to improve processes of care in some healthcare settings, but there is little evidence related to its use or effects in pre-hospital emergency care. CCDS in this setting aligns with policies to increase IT use in ambulance care, enhance paramedic decision-making skills, reduce avoidable emergency department attendances and improve quality of care and patient experience. This qualitative study was conducted alongside a cluster randomised tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised [19,23,25,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised [19,23,25,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identi ed in the peer-reviewed and grey literature were focused on clinician experiences of change related to a speci c event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that bene ts could be realised (19,23,25,76,77).…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised (18,22,24,75,76).…”
Section: Discussionmentioning
confidence: 99%